AIDS: Global impact and the implications for SE Asia - Ismail, Rokiah
The AIDS epidemic has been with us for more than a decade. The first AIDS case was reported in 1981 in California, USA, in a gay man. The condition was at first known as the 'gay men's disease' but was very soon seen to be spreading rapidly in the heterosexual population. In the very early stages of the epidemic it was thought that AID was a disease of the Western world, until the African continent was found co be hard hit in the mid-1980 and it was realized that spread to the rest of the developing world- where it will inevitably have enormous impact - was imminent. The recent rapid rise of HIV infection in India and Thailand is cause for concern. Poverty large family households, and the need to earn to survive. leads to the commercialization of sex. Workers migrate to cities to find jobs and family units are djsrupted: this, together with poor access co healthcare, may cause the spread of HIV infection in the developing countries of Asia eventually to outstrip what has been seen in Africa.